Embedded Contract Languages - Fahndrich, Manuel; Barnett, Mike; Logozzo, Francesco (ACM SAC - OOPS, 2010)
Specifying application interfaces (APIs) with information that goes beyond method argument and return types is a long-standing quest of programming language researchers and practitioners. The number of type system extensions or specification languages is roughly equal to the number of tools that consume them. In other words, every tool comes with its own specification language. In this paper we argue that for modern object-oriented languages, using an embedding of contracts as code is a better approach. We exemplify our embedding of Code Contracts on the Microsoft managed execution platform (.NET) using the C# programming language. The embedding works as well in Visual Basic. We discuss the numerous advantages of our approach and the technical challenges, as well as the status of tools that consume the embedded contracts